Dual‐band differential bandpass filter using stepped impedance resonators. Issue 6 (24th February 2015) - Cui, Hengrong; Sun, Yun; Wang, Shuna; Lu, Yunlong
ABSTRACT In this article, a novel dual‐band differential bandpass filter using (SIRs) is designed. To demonstrate the design ideas, the differential and common mode equivalent half circuits are built and studied. Two resistors are connected between the two ends of the SIRs to consume the power in common mode. A capacitor is connected between the Ground and Center of the SIR to adjust the spurious frequencies, also strength the coupling of the two SIRs. The theoretical analysis shows the second band can be obtained by the proper impedance ratios of the resonances and the capacitor connected to the resonator. Two through ground vias (TGVs) connecting the top and bottom sides of the SIR filter, are used to realize the common mode rejection. To investigate the proposed filter in detail, a set of design equations are derived based on the circuit theory and transmission line theory. A phototype dual‐band differential filter operating at 1.5 and 2.75 GHz has been realized to validate the proposed concept and theory. © 2015 Wiley Periodicals, Inc. Int J RF and Microwave CAE 25:468–473, 2015.